Maternal Hyperlipidemia and the Risk of Preeclampsia: a Meta-Analysis - Cassandra N. Spracklen; Caitlin J. Smith; Audrey F. Saftlas; Jennifer G. Robinson; Kelli K. Ryckman (2014)
Published reports examining lipid levels during pregnancy and preeclampsia have been inconsistent. The objective of this meta-analysis was to test the association between preeclampsia and maternal total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), non-HDL-C, and triglyceride levels measured during pregnancy. We conducted a systematic search for studies published between the index date until July 2013 reporting maternal lipid levels in women with preeclampsia and normotensive pregnant women. Seventy-four studies met all eligibility criteria and were included in the meta-analysis. Weighted mean differences in lipid levels were calculated using a random-effects model. Statistical heterogeneity was investigated using the I2 statistic. Meta-regression was used to identify sources of heterogeneity. Preeclampsia was associated with elevated total cholesterol, non-HDL-C, and triglyceride levels, regardless of gestational age at the time of blood sampling, and with lower levels of HDL-C in the third trimester. A marginal association was found with LDL-C levels. Statistical heterogeneity was detected in all analyses. Meta-regression analyses suggested that differences in body mass index (weight (kg)/height (m)2) across studies may be partially responsible for the heterogeneity in the triglyceride and LDL-C analyses. This systematic review and meta-analysis demonstrates that women who develop preeclampsia have elevated levels of total cholesterol, non-HDL-C, and triglycerides during all trimesters of pregnancy, as well as lower levels of HDL-C during the third trimester.